PENGGUNAAN PERMAINAN MONOPOLI SEBAGAI MEDIA CHEMO-EDUTAINMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA MAN 2 MODEL PEKANBARU - Ella Dini Miranda Dini Miranda; Jimmi Copriady Jimmi Copriady; Susilawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This Research in find out the influence of the use of game monopoly as media chemo-edutainment how it affect the student achievement on the topic of colloid in class XI Science MAN 2 Model Pekanbaru. This kind of research is experiment research with randomized control group pretest-posttest design. The population in this research is all student of class XI Science MAN 2 Model Pekanbaru. The sample consisted of two classes, namely class XI Science 1 as the experimental class and class XI science 2 as a controls class, it randomly selected after normality test and homogeneity test. Experimental class is a class that was treated by learning using media game of monopoly, while the control class is a class that is not treated using media game of monopoly. Data analysis technique is the right t-test. Based on the final calculation result obtained tvalue is 3.070 > ttable is 1.676 (dk = n1 + n2 – 2, α = 0,05) with an increase in the use of media influence a game of monopoli to student achievement is 16.7%, so it can be concluded that the use of game monopoli as media chemo-edutainment improve the student’s achievement on the subject of colloid in class XI Science MAN 2 Model Pekanbaru.Keyword : Learning, Monopoly game, Media chemo-edutainment, Learning Achievement, Colloid